Cyberthreats: the emerging fault lines of the nation state - Brenner, Susan W. (Oxford Univ. Press, 2009)
Order & disorder : crime, war and terrorism -- Cyberthreats : new issues, new challenges -- Attribution : attacks -- Attribution : attackers -- Response : where we are -- How did we get here? -- Where do we go from here?